Surface Of Underground Coal Mine Fires - Maria I. De Rosa (The National Institute for Occupational Safety and Health (NIOSH), 2004)
Table 10 and figure 4 show the number of fires and fire injuries occurring at the surface of underground coal mines by state during 199&1999. Table 10 also shows by state the risk rate, employees' working hours, and lost workdays. A total of 65 fires occurred in 10 states. Thirteen of those fires caused 12 injuries and 1 fatality (the yearly average was 6.5 fires and 1.2 injuries). Four fues and one fire injury involved con- tractors. The Ewhr value was 97 x l O6 hr (Irr = 0.025); the LWD value was 6,206. Pennsylvania had the most fues (20 fues and 5 injuries), followed by West Virginia (1 6 fires and 1 fatality) and Kentucky (1 5 fires and 3 injuries). Among these states, Pennsylvania had the highest injury risk rate value (Irr - 0.095). Table 1 1, partly illustrated in figure 5, shows by time period the number of fires, fire injuries, and fire fatalities; risk rates; employees' working hours; and lost workdays. The number of fires and fire injuries show a decrease followed by an increase during the five time periods, accompanied by a decline in employees' working hours throughout the periods (see table 11 and figure 5). The Irr values follow patterns similar to those shown by the injury values. Tables 12- 17 show the number of fires by ignition source, method of detection and suppression, equipment involved, location, and burning material by time period. Figure 6 shows the major variables during 199&1999. Table 18 shows the number of fire injuries per number of fires causing injuries and total fires by year, ignition source, equipment involved, and location.